Dealing with Resistance: Working with Involuntary Clients in Community-Based Drug Treatment Programs in China. Issue 3 (2nd July 2020) - Liu, Liu; Chui, Wing Hong; Deng, Yali; Li, Hongxuan
ABSTRACT: This study explores strategies for dealing with client resistance that are commonly used by a group of selected counsellors who work closely with illicit drug users in the community-based compulsory treatment programs in China. Through semistructured in-depth interviews with 16 counsellors, this study finds that different forms of client resistance were experienced in their day-to-day practice, encompassing passive and active behaviours. Five typical strategies are used by Chinese counsellors in this study to deal with client resistance: showing respect and caring and expressing empathy; attending to the needs of the clients; making effective use of peer influence; altering clients' unwillingness to change; and strategically enhancing clients' self-determination. Considering these strategies can also be seen as general principles for dealing with involuntary clients in other fields of social work services, the findings of this study may have broader impact. IMPLICATIONS Effective ways that can be used by counsellors for reducing illicit drug users' resistance during treatment include: showing respect and caring, and expressing empathy; attending to the needs of the clients; making effective use of peer influence; altering clients' unwillingness to change; and strategically enhancing clients' self-determination. Professional social work training is urgently needed among community-based drug treatment social work practitioners in China, to achieve efficient practices and better outcomes.